Integrating MSMEs’ business agility into SDGs framework: A pathway toward sustainable environmental economy - Ramli Yana (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Micro, small, and medium enterprises (MSMEs) are pivotal to Indonesia’s economy, contributing 61% to GDP and 97% to employment, yet face significant barriers in adopting sustainable practices amid environmental challenges like 216 million tons of annual CO₂ emissions. This study aims to analyze how business agility enables MSMEs to transition toward a green economy, aligning with Sustainable Development Goals (SDGs) 8, 9, and 13. Existing literature highlights agility’s role in SME innovation but lacks a multidimensional framework for MSMEs in developing economies, particularly Indonesia, where low green adoption (<5% ISO 14001 certification) and financing gaps (IDR 2,400 trillion shortfall by 2026) persist. Methods: An integrative literature review (ILR) was conducted, synthesizing secondary qualitative data from sources like Bappenas report, peer-reviewed studies, and reports from OECD, World Bank, and UNDP. Using Whittemore and Knafl’s framework, the study employed thematic analysis within a dynamic capabilities theory lens, categorizing findings into firm-level (e.g., eco-innovation), network-level (e.g., collaborative ecosystems), and institutional-level (e.g., policy adaptability) dimensions. Findings: Results reveal that firm-level agility drives eco-innovation but is limited by low digital transformation (16% adoption). Network-level agility, through partnerships like West Java’s 38 cleantech startups, supports SDG 9, while institutional-level agility addresses financing gaps, aligning with SDG 13. Regional disparities, such as South Sulawesi’s 74% lack of green processes, highlight the need for tailored agility strategies. Triangulated data confirm agility’s role in bridging micro-level practices with macro-level SDG goals, extending dynamic capabilities theory. Conclusion: Business agility empowers MSMEs to navigate environmental and market challenges, fostering sustainable transitions critical for Indonesia’s net-zero goal by 2060. Novelty/Originality: This study offers a novel multidimensional framework linking agility across firm, network, and institutional levels to SDGs, addressing underexplored Indonesia-specific challenges and proposing actionable policy interventions for green MSME empowerment.